Optimalisasi Digital Branding Berbasis Storytelling Produk Dalam Meningkatkan Daya Saing Umkm Batik Giriloyo Di Kabupaten Bantul, Daerah Istimewa Yogyakarta - Hudan Mudaris; Setyoadi Purwanto (Elsalima (Salam Institute), 2026)
Batik Giriloyo is one of the intangible cultural heritage products with high historical and aesthetic value in Bantul Regency, Special Region of Yogyakarta. However, amid the rapid wave of economic digitalization, SME artisans in the Giriloyo batik center still face significant capacity limitations in utilizing digital platforms for promotion and market expansion. This community service program aims to optimize product storytelling-based digital branding capabilities among Giriloyo batik artisans to enhance their competitiveness and strengthen local product identity in the digital economy era. The program was implemented on June 15, 2025, involving 50 participants from the local batik artisan and SME community, employing an Asset Based Community Development (ABCD) approach that focuses on identifying and optimizing the existing potential and assets of the community. Activities included community asset mapping, digital literacy training, storytelling content creation workshops, hands-on content production practice, and independent mentoring. Evaluation results using the Kirkpatrick model integrated with Bloom's Taxonomy revealed significant improvements across all competency dimensions: cognitive domain increased by an average of 29%, affective domain by 27.5%, and psychomotor domain by 34%. A total of 42 out of 50 participants successfully produced and independently uploaded product content, and visual identity guidelines were established for six artisan groups. This program implies the critical importance of integrating local cultural values into digital branding strategies as a sustainable competitive foundation for locally-based SMEs.